Characterisation of RuvAB-Holliday junction complexes by glycerol gradient sedimentation. - Hiom, K (1995)
The Escherichia coli RuvA and RuvB proteins interact specifically with Holliday junctions to promote ATP-dependent branch migration during genetic recombination and DNA repair. In the work described here, glycerol gradient centrifugation was used to investigate the requirements for the formation of pre-branch migration complexes. Since gradient centrifugation provides a simple and gentle method to analyse relatively unstable protein-DNA complexes, we were able to detect RuvA- and RuvAB-Holliday junction complexes without the need for chemical fixation. Using 35S-labelled RuvA protein and 3H-labelled Holliday junctions, we show that RuvA acts as a helicase accessory factor that loads the RuvB helicase onto the Holliday junction by structure-specific interactions. The resulting complex contained both RuvA and RuvB, as detected by Western blotting using serum raised against RuvA and RuvB. The stoichiometry of binding was estimated to be approximately four RuvA tetramers per junction. Formation of the RuvAB-Holliday junction complex required the presence of divalent metal ions and occurred without the need for ATP. However, the stability of the complex was enhanced by the presence of ATP gamma S, a non-hydrolysable ATP analogue. The data support a model for branch migration in which structure-specific binding of Holliday junctions by RuvA targets the assembly of hexameric RuvB rings on DNA. Specific loading of the RuvB ring helicase by RuvA is likely to be the initial step towards ATP-dependent branch migration.